Newborn screening for congenital heart disease using echocardiography and follow-up at high altitude in China. (1st January 2019) - Li, Jing-Jing; Liu, Yuan; Xie, Si-Yuan; Zhao, Guo-Dong; Dai, Ting; Chen, Hong; Mu, Lan-Fang; Qi, Hai-Ying; Li, Jia
Abstract: Background: Pulse oximetry screening for critical congenital heart disease (CHD) is inapplicable to high altitude due to the variedly decreased arterial saturations and rare complex CHD. We examined the incidence and spectrum of CHD in newborns using echocardiography at high altitude and followed up their outcomes. Methods: A total of 1337 babies were studied. Echocardiography was performed in 1002 asymptomatic newborns (3–5 days). In the same period, retrospectively studied 394 newborns (≤2 days) admitted to the NICU where echocardiograph was performed in 335. In both groups, follow-up was made at 1–3, 6 and 12–18 months. Results: The incidence of CHD in asymptomatic newborns was 27.8%, consisting secundum atrial septal defect (ASD) [175 (62.7%)], patent ductus arteriosus (PDA) [61 (21.9%)], ventricular septal defect (VSD) [8 (2.9%)] and multiple defects [35 (12.6%)]. And 19.4% in NICU patients with similar spectrum, except for 2 with complex CHD who died before discharge. By 12–18 months of follow-up, 30% of CHD remained open. Thirteen patients developed mild to severe pulmonary arterial hypertension (PAH), and 2 of them died of heart failure. Conclusions: The incidence of CHD in newborns at high altitude is about 20 times higher than that at low altitude, consisting mostly of simple forms with left to right shunt, with rare complex CHD. By 12–18 months, the incidence of CHD is still about 10 times higher than that at low altitude. About 8% patients developed PAH or death. Follow-up must be reinforced in order to provide early intervention and prevent from PAH or death.